2019
DOI: 10.3390/met9090976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Build Orientation on the Corrosion Behavior and Mechanical Properties of Selective Laser Melted Ti-6Al-4V

Abstract: Ti-6Al-4V alloys with different build orientations have been fabricated by selective laser melting (SLM). The corrosion behavior and mechanical properties have been studied. Investigation of microstructures were characterized by optical microscopy (OM), scanning electron microscopy (SEM), and X-ray diffraction (XRD) analysis. Electrochemical results show that the vertical sample and horizontal sample possess excellent corrosion resistance in the cross section and longitudinal section respectively, which can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
4
16
0
Order By: Relevance
“…The anodizing process reduced the passive current density and heat treatment increased β phase. There was a difference in corrosion resistance offered by horizontally build and vertically build specimens due to difference in amount of α and β phases in cross sectional and longitudinal direction, which shows that anisotropic nature of DMLS material will affect its corrosion resistance [33] . R. Żebrowski et al [34] used surface treatment shot peening to improve surface quality of DMLS Ti-6Al-4V and reported that shot peening at low frequencies was found to be effective in reducing surface roughness and improved its corrosion resistance.…”
Section: Characteristics Of Ti-6al-4vmentioning
confidence: 99%
“…The anodizing process reduced the passive current density and heat treatment increased β phase. There was a difference in corrosion resistance offered by horizontally build and vertically build specimens due to difference in amount of α and β phases in cross sectional and longitudinal direction, which shows that anisotropic nature of DMLS material will affect its corrosion resistance [33] . R. Żebrowski et al [34] used surface treatment shot peening to improve surface quality of DMLS Ti-6Al-4V and reported that shot peening at low frequencies was found to be effective in reducing surface roughness and improved its corrosion resistance.…”
Section: Characteristics Of Ti-6al-4vmentioning
confidence: 99%
“…Moreover, some studies also worked on the effect of the ti6al4v alloy track trajectories on mechanical properties in direct metal deposition [ 4 ], the effect of microstructure, crystallographic texture and morphological texture on the mechanical properties of 3D printed 316L stainless steel [ 5 ] and the effect of scanning strategy on grain structure and crystallographic texture of Inconel 718 processed by selective laser melting [ 6 ]. Some researchers also worked on the effect of build orientation on the corrosion behavior and the mechanical properties of Selective Laser Melted Ti-6AI-4V [ 7 ]. The influence of heat treatments on heat affected zone cracking of gas tungsten arc welded additive manufactured alloy 718 was also investigated [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their insertion into the human skeleton may result in the absence of strong bonds between the bone and implant. Commonly, the Ti6Al4V alloy is one of the most widely used in the medical world, since it significantly increases the strength, ductility and fatigue resistance of the implants, which could prevent their fracture [2,7,8].…”
Section: Introductionmentioning
confidence: 99%